2022
DOI: 10.6004/jnccn.2022.7033
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polypharmacy and Potentially Inappropriate Medications With Frailty Among Older Adults With Blood Cancers

Abstract: Background: Polypharmacy and potentially inappropriate medications (PIMs) are common among older adults with blood cancers, but their association with frailty and how to manage them optimally remain unclear. Patients and Methods: From 2015 to 2019, patients aged ≥75 years presenting for initial oncology consult underwent screening geriatric assessment. Patients were determined to be robust, prefrail, or frail via deficit accumulation and phenotypic approaches. We quantified each patient’s total number of medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
0
10
0
2
Order By: Relevance
“…A previous study of 4,402 North Americans showed that taking a greater number of medications was associated with an increased risk of incident frailty compared to taking 0–3 medications (HR [95% CI]; 1.55 [1.22–1.96] for 4–6 medications, 2.47 [1.78–3.43] for ≥ 7 medications) [ 12 ]. Further, a study of 785 patients aged ≥ 75 years with blood cancers reported that the OR for frailty was 2.82 times higher in older people with polypharmacy (≥ 8 medications) compared to in those without polypharmacy (OR 2.82, 95% CI: 1.92–4.17) [ 21 ]. In addition, as the anticholinergic risk score increased by one point, the OR for frailty increased by 19% (OR 1.19, 95% CI: 1.03–1.39) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of 4,402 North Americans showed that taking a greater number of medications was associated with an increased risk of incident frailty compared to taking 0–3 medications (HR [95% CI]; 1.55 [1.22–1.96] for 4–6 medications, 2.47 [1.78–3.43] for ≥ 7 medications) [ 12 ]. Further, a study of 785 patients aged ≥ 75 years with blood cancers reported that the OR for frailty was 2.82 times higher in older people with polypharmacy (≥ 8 medications) compared to in those without polypharmacy (OR 2.82, 95% CI: 1.92–4.17) [ 21 ]. In addition, as the anticholinergic risk score increased by one point, the OR for frailty increased by 19% (OR 1.19, 95% CI: 1.03–1.39) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a study of 785 patients aged ≥ 75 years with blood cancers reported that the OR for frailty was 2.82 times higher in older people with polypharmacy (≥ 8 medications) compared to in those without polypharmacy (OR 2.82, 95% CI: 1.92–4.17) [ 21 ]. In addition, as the anticholinergic risk score increased by one point, the OR for frailty increased by 19% (OR 1.19, 95% CI: 1.03–1.39) [ 21 ]. However, unlike this previous finding, our study found that polypharmacy based on taking five medications was not associated with frailty in older people.…”
Section: Discussionmentioning
confidence: 99%
“…Given the aforementioned increased use of longterm anticancer treatment and the rates of comorbid conditions in the aging cancer population, the age of our study population (mean = 65 years) and number of medications (mean = 11) is of great importance. Several publications have highlighted the medicationrelated risks and resultant toxicity in older patients with cancer who receive multiple medications [22][23][24]. Notably, a recent study by Dr. Lu-Yao and colleagues demonstrated the relationship between polypharmacy (≥ 5 concurrent medications) and rates of inpatient hospitalization among older adults (> 65 years) treated with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As there is an increased prevalence of cancer and polypharmacy among older adults, patients undergoing chemotherapy treatment may experience a variety of nail changes [ 27 ]. Muehrcke’s lines are defined as opaque white transverse bands (apparent leukonychia) separated by normal pink colored nail, due to acute toxicity to tissues with high mitotic activity, such as the nail matrix.…”
Section: Traumatic Changesmentioning
confidence: 99%